Dilated Cardiomyopathy Risk in Patients with Coronavirus Disease 2019: How to Identify and Characterise it Early? - Maki Komiyama; Koji Hasegawa; Akira Matsumori (European Cardiology Review, 2020)
Multiple lines of evidence have shown that elevated blood troponin is strongly associated with poor prognosis in patients with the novel coronavirus disease 2019 (COVID-19). Possible mechanisms of myocardial injury in COVID-19 include ischaemia due to circulatory and respiratory failure, epicardial or intramyocardial small coronary artery thrombotic obstruction due to increased coagulability, and myocarditis caused by systemic inflammation or direct binding of the virus to its receptor, angiotensin-converting enzyme-2 (ACE2), which is abundantly expressed in the heart. It is postulated that persistent immune activation upon viral infection increases the risk of developing dilated cardiomyopathy in COVID-19 patients.